Polishing performance and mechanism of a water-based nanosuspension using diamond particles and GO nanosheets as additives. (December 2021) - Huang, Shuiquan; Li, Xuliang; Mu, Dekui; Cui, Changcai; Huang, Hui; Huang, Han
Abstract: Single-crystal silicon carbide (SiC) is as a promising optoelectronic material for applications in solar cells, power converters and transistors. However, its high hardness combined with low fracture toughness has rendered significant challenges for high-efficiency and low-damage polishing. In this work, a novel polishing process was developed for single crystal SiC by using a water-based nanosuspension that used graphene oxide (GO) nanosheets and diamond particles as additives. The polishing characteristics of the diamond/GO hybrid nanosuspensions were investigated, using commercially available diamond suspensions as benchmarks. The hybrid nanosuspensions resulted in a superior polishing performance, as both surface quality and efficiency were substantially improved, owing to the synergistic effect of the oxidation and lubrication generated by GO nanosheets and the mechanical abrasion of diamond particles. Highlights: It presents a novel polishing process for single-crystal SiC by using diamond/GO hybrid nanosuspensions. The polishing performance of the hybrid nanosuspensions is superior to the conventionally used diamond suspensions. The oxidation, lubrication, and removal mechanisms involved in the new process were unveiled. It offers a practical and efficient approach for future nanoscale machining of hard-brittle materials.